Enhancing Understanding of Siloxane Surface Properties and Functional Group Effects on Water Deoxygenation - Fryad Mohammed Sharif; Sohail Murad; Saif Talal Manji (ChemEngineering, 2024)
The deoxygenation process in water used in well injection operations is an important matter to eliminate corrosion in the petroleum industry. This study used molecular dynamics simulations to understand the behavior of siloxane surfaces by studying the surface properties with two functional groups attached to the end of siloxane and their effect on the deoxygenation process. The simulations were performed using LAMMPS to characterize surface properties. Jmol software version 14 was used to generate siloxane chains with (8, 20, and 35) repeat units. We evaluated properties such as total energy, surface tension, and viscosity. Then, we used siloxane as a membrane to compare the efficiency of deoxygenation for both types of functional groups. The results indicated that longer chain lengths increased the total energy and viscosity while decreasing surface tension. Replacing methyl groups with trifluoromethyl (CF3) groups increased all the above mentioned properties in varying proportions. Trifluoromethyl (CF3) groups showed better removal efficiency than methyl (CH3) groups but allowed more water to pass. Furthermore, the simulations were run using the class II potential developed by Sun, Rigby, and others within an explicit-atom (EA) model. This force field is universally applicable to the atomistic simulation of polymers, inorganic small molecules, and common organic molecules.